(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the establishment of trade relations via England in the second half of 16th century between Russia and Bukhara is examined. Anthony Jenkinson, who was a representative of English Moscow company, which held a monopoly on trade with Russia, had a mission there and he depicted the image of Bukhara in his notes.